Application of Recombinant Human BMP-2 with Bone Marrow Aspirate Concentrate and Platelet-Rich Fibrin in Titanium Mesh for Vertical Maxillary Defect Reconstruction prior to Implant Placement - Kamel Alraei; Jameel Shrqawi; Khawlah Alarusi (Case Reports in Dentistry)
Recombinant human bone morphogenetic protein 2 (rhBMP-2) is an alternative bone substitute for extensive maxillary bone defects which avoids the disadvantages associated with other grafting materials. This report details a case of a 32-year-old female with a severe vertical and horizontal maxillary bony defect that developed after tumor removal. She underwent two unsuccessful regenerative surgeries with an iliac bone graft. Reconstruction of the maxillary defect was planned by offlabel use of rhBMP-2/absorbable collagen sponge (ACS) combined with a bone marrow aspirate concentrate (BMAC) and allograft in a titanium mesh covered in platelet-rich fibrin (PRF). Clinical and radiographic evaluations showed good quality and quantity of bone formation, and she was rehabilitated with dental implants and prosthodontic treatment. Based on this case, the use of rhBMP-2 as a graft material appears encouraging with a satisfying outcome. The present case is aimed at reporting the clinical and radiographic effectiveness of rhBMP-2/ACS in combination with PRF and a titanium mesh for severe maxillary bone defects. Future investigations will be required to ascertain the long-term survival of implants in areas grafted with rhBMP-2.